2018
DOI: 10.1007/s12010-018-2763-x
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification of Waste Frying Oil and Soybean Oil by Combi-lipases Under Ultrasound-Assisted Reactions

Abstract: This work describes the use of an ultrasound system for the enzymatic transesterification of oils using combi-lipases as biocatalyst. The reactions were carried out evaluating the individual use of waste oil and fresh soybean oil, and the immobilized lipases CALB, TLL, and RML were used as biocatalysts. It was performed in a mixture design of three factors to obtain the ideal mixture of lipases according to the composition of fatty acids present in each oil, and the main reaction variables were optimized. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 35 publications
0
48
1
Order By: Relevance
“…Waste oil and fresh soybean oil were transformed into biodiesel using an ultrasound system with a combi-lipase as a biocatalyst (including N435 and Lipozyme TL IM, and Lipozyme RM IM). 44 The optimal mixture of lipases depended on the oil; for soybean oil the combi-lipase composition was 50% CALB, 22.5% TLL, and 27.5% RML, while for used frying oil, it was 40% TLL, 35% CALB, and 25% RML. The paper showed that ultrasound provided a soybean oil biodiesel yield of 90% and 70% when employing waste oil.…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste oil and fresh soybean oil were transformed into biodiesel using an ultrasound system with a combi-lipase as a biocatalyst (including N435 and Lipozyme TL IM, and Lipozyme RM IM). 44 The optimal mixture of lipases depended on the oil; for soybean oil the combi-lipase composition was 50% CALB, 22.5% TLL, and 27.5% RML, while for used frying oil, it was 40% TLL, 35% CALB, and 25% RML. The paper showed that ultrasound provided a soybean oil biodiesel yield of 90% and 70% when employing waste oil.…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
“…40,41 The biological function of lipases is the hydrolysis of triglycerides to produce free fatty acids and glycerol. 42 The heterogeneity of the natural substrate [43][44][45][46][47][48] has converted lipases in enzymes with a very broad specificity, accepting substrates very different from glycerides (even amides). Thus, lipases are used in vitro to catalyze reactions different from those of the natural hydrolase function, [49][50][51][52][53][54] such as esterification, [55][56][57][58][59][60][61] acidolysis, [62][63][64][65][66][67] interesterificaton, [68][69][70][71] transesterification, [72][73][74][75][76] aminolysis, [77][78][79][80][81] perhydrolysis, 82,83 etc., together with a collection of the so-called promiscuous reactions.…”
Section: Lipases In Biocatalysismentioning
confidence: 99%
“…However, these features become a problem when the biocatalyst is going to be utilized in the full modification of a heterogeneous substrate. This is the case of oils, either when they are hydrolyzed to produce free fatty acids or when they are used in transesterifications to produce biodiesel [16][17][18][19][20][21][22][23]. It should be considered that the oil will be composed of many different triglycerides formed by different fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is not easy to find an "optimal" enzyme that may be the best one in all situations. In these cases, it has been shown that the combined use of several lipases permits not only better yields but also higher initial reaction rates and more lineal reaction courses (in some cases one enzyme eliminates an inhibitor of the main enzyme) [16][17][18][19][20][21][22][23]. Usually, this has been obtained using mixtures of individually immobilized lipases [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…• Recently (2018), Poppe et al [22] described the use of an ultrasound system for the enzymatic transesterification of oils using combi-lipases as a biocatalyst. Reactions were performed in a mixture design of three factors to obtain the ideal mixture of lipases (CALB, TLL, and RML) according to the composition of fatty acids present in each oil, and the main reaction variables were optimized.…”
Section: Waste Cooking Oil or Frying Waste Oil (Wco Or Fwo)mentioning
confidence: 99%